Mathematical investigations in the classroom: A collaborative project - Oliveira, Hélia (2011)
This paper presents some work developed through a collaborative project involving mathematics teachers and teacher educators, aimed at the development of classroom tasks involving students in mathematical investigations and the study of related teaching styles. We give a general overview of the project and present one task dealing with the concepts of powers and exponents. Then, we describe how it was used in the classroom (grade levels 5-7), and present our experience about the role and the activity of the teacher in the process of organizing, conducting and reflecting about this kind of activity.